Breaking the Chains of Poverty Through the Family Hope Program - Kamila, Fatia Marsya; Meilinda, Ananta Tri; Nursahidin, Nursahidin; Sutarjo, Moh (Riviera Publishing, 2025)
This study evaluates the effectiveness of the Family Hope Program (PKH) in Harjamukti District, Cirebon City, where the Family Hope Program (PKH) aims to break the chain of poverty and improve family welfare. The method used is a qualitative approach with a focus on three parameters: clarity of program objectives, success in achieving objectives, and efficiency of implementation. The results of the study show that the Family Hope Program (PKH) in Harjamukti District, Cirebon City has been running effectively, besides that the Family Hope Program (PKH) has had a positive impact, such as increasing the attendance of children at school and regular visits of pregnant women to posyandu. However, there are challenges in terms of the accuracy of the goals and the community's understanding of the program's objectives, therefore it is necessary to strengthen socialization and education for beneficiaries so that the long-term goals of PKH can be understood and implemented properly, so as to support the economic independence of poor families in a sustainable.